Digital Investigative Journalism Data, Visual Analytics and Innovative Methodologies in International Reporting - Hahn, Oliver; Stalph, Florian (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
XIII, 267 p. 9 illus., 6 illus. in color.